ROLE OF POLITICAL CONNECTIONS, FAMILY OWNERSHIP, FOUNDERS ON BOARD AND FIRM PERFORMANCE - Teddy Jurnali; Sheila Septiany (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
Family ownership and political connections have made significant contributions to company in Indonesia. Hence, firms registered on the Indonesia Stock Exchange (IDX) were tested as samples with firm performance as a measurement. The purpose of this article is to research the role of family ownership and founders on board on firm performance with political connections as a moderating variable. The sample data used in this research are quantitative data with 492 registered firms on IDX for the period of 2015 to 2019. The analysis results show that family ownership influences firm performance positively. However, founders on board have insignificant relation with firm performance. Meanwhile, political connections do not moderate the relationship between family ownership and founders on board with firm performance.